Pengaruh Kompetensi Wirausaha, Motivasi Berwirausaha dan Dukungan Sosial Mahasiswa terhadap Minat Berwirausaha pada Mahasiswa Wirausaha Merdeka (Jurnal Simki Economic, 2025)
Student entrepreneurial interest is an important factor in creating a young generation that is economically independent and able to create new jobs. The Independent Entrepreneurship Program (WMK) is one of the government's efforts to form an entrepreneurial ecosystem in the university environment. However, the level of student interest in actually entering the business world still varies. This study aims to analyze the effect of entrepreneurial competence, entrepreneurial motivation, and social support on entrepreneurial interest in students participating in the WMK Program. This study uses a quantitative method with an explanatory approach and saturated sampling technique, with a total of 371 respondents participating in the 2024 Pandalungan WMK Program. Data were collected through a questionnaire using a Likert scale and analyzed using validity, reliability, multiple linear regression, and partial (t-test) and simultaneous (F-test) tests. The results of the study indicate that entrepreneurial competence, entrepreneurial motivation and social support have a positive and significant effect on entrepreneurial interest. Simultaneously, these three variables have a significant effect on students' interest in entrepreneurship. Based on these results, it is recommended that the organizers of the WMK Program place more emphasis on improving practical competence and strengthening student motivation, as well as creating a social environment that is more supportive of the development of students' entrepreneurial spirit.